2020
DOI: 10.1039/d0nr03058a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of recombination losses and charge collection efficiency in a perovskite solar cell by comparing impedance response to a drift-diffusion model

Abstract: Interpreting the impedance response of perovskite solar cells is significantly more challenging than for most other photovoltaics. Here we provide a way to obtain useful information from the spectrum using insights from drift-diffusion simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(116 citation statements)
references
References 61 publications
(123 reference statements)
6
110
0
Order By: Relevance
“…[12] However, Riquelme et al have shown that the R HF (not R LF ) can be considered as a true recombination resistance as both the resistances have different biases and illumination dependences. [19] Moreover, a similar slope, but with the opposite trend, is observed between R LF and C LF here, which indicates the same physical origin among them, but not with R HF . Based on our results and studies from the other authors following points are drawn: 1) R HF and R LF follow a similar dependence on the applied bias and illumination with a comparable slope.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…[12] However, Riquelme et al have shown that the R HF (not R LF ) can be considered as a true recombination resistance as both the resistances have different biases and illumination dependences. [19] Moreover, a similar slope, but with the opposite trend, is observed between R LF and C LF here, which indicates the same physical origin among them, but not with R HF . Based on our results and studies from the other authors following points are drawn: 1) R HF and R LF follow a similar dependence on the applied bias and illumination with a comparable slope.…”
Section: Resultssupporting
confidence: 59%
“…[42] However, the decrease in recombination is clearly visible in the EIS spectra shown in Figure 3f Riquelme et al have simulated the low-frequency spectra peak in Im|Z| versus frequency plots, and showed that this peak shifts toward the high frequency as it is related to the high diffusion coefficient of ions. [19] The authors also stated that the associated low-frequency resistance, i.e., R LF should be the function of ions diffusion. Comparing the plots shown in Figure 2 and 3, it is established that shift in low-frequency peak in Im|Z| versus frequency plots and value of R LF and C LF has a no direct relation.…”
Section: Effect Of Grain Size and Boundaries In Perovskite Layer On The Low-frequency Arc In Eis Of Pscmentioning
confidence: 99%
See 2 more Smart Citations
“…The n id values measured from light intensity‐dependent V oc characteristics are popularly employed to understand which type of charge recombination prevails between the non‐radiative recombination via mid gap states created by defects, and radiative recombination via direct band‐to‐band transitions. [ 36–38 ] A value of n id approaching two was considered to result from a high defect density for non‐radiative SRH recombination, which in many cases could explain a low V oc . However, this analysis requires the premise that interfacial SRH recombination makes little contribution to V oc and n id .…”
Section: Introductionmentioning
confidence: 99%